Strategic lean mapping : blending improvement processes for the perfect solution - Borris, Steven (McGraw-Hill's AccessEngineering., 2013)
"Proven methods are detailed for diagnosing problems, improving processes, and increasing profits. A continuous improvement expert reveals how to visually document your organization's processes and identify problematic issues. Find out how to blend and then apply select techniques from Lean Manufacturing, Theory of Constraints, RCM (Reliability-Centered Maintenance), TPM (Total Productive Maintenance), OEE (Overall Equipment Efficiency), and other methodologies to implement the perfect solution to the task at hand. Diagrams, charts, and real-world case studies help you to put the concepts presented into practice. This hands-on guide will help small companies, large global organizations, and government agencies alike find ideal solutions for individual processes or projects.".